The effect of financial leverage on financial performance: evidence of banking sector in Malaysia / Adh-lah Adnan - Adnan, Adh-lah (2017)
This paper is aims to examine the effect of financial leverage on financial performance of banking sector in Malaysia. This study focus on five Commercial banks in Malaysia that registered under Bank Negara Malaysia. The dependent variable in this study is performance of five commercial bank in Malaysia that measure by return on assets (ROA) while the independent variables in this study are debt ratio (DR), debt equity ratio (DER) and interest coverage ratio (ICR). The data from the sample of five commercial Bank in Malaysia extract from data stream database in library Universiti Teknologi MARA campus Segamat for 10 years (2006-2015). Total number of observation is 50. This study used quantitative secondary data which is panel data and multiple regression model represented by the ordinary least squares (OLS) to look financial leverage that effect on commercial bank's performance in Malaysia.